2017
DOI: 10.1007/s11064-017-2219-7
|View full text |Cite
|
Sign up to set email alerts
|

Three Types of A11 Neurons Project to the Rat Spinal Cord

Abstract: The A11 dopaminergic cell group is the only group among the A8-A16 dopaminergic cell groups that includes neurons innervating the spinal cord, and a decrease in dopaminergic transmission at the spinal cord is thought to contribute to the pathogenesis of restless legs syndrome. However, the mechanisms regulating the neuronal activity of A11 dopaminergic neurons remain to be elucidated. Unraveling the neuronal composition, distribution and connectivity of A11 neurons would provide insights into the mechanisms re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Among these regions, we focused on the locus coeruleus (LC; the A6 region), because activation of the nucleus suppresses visceromotor reflex response to colorectal distension (35). Additionally, roles of the A11 region, the principle source of dopamine in the spinal cord (4,8,25), were examined. Our results revealed that the brainstem monoaminergic nuclei activate the spinal defecation center, resulting in enhancement of colorectal motility.…”
Section: Introductionmentioning
confidence: 99%
“…Among these regions, we focused on the locus coeruleus (LC; the A6 region), because activation of the nucleus suppresses visceromotor reflex response to colorectal distension (35). Additionally, roles of the A11 region, the principle source of dopamine in the spinal cord (4,8,25), were examined. Our results revealed that the brainstem monoaminergic nuclei activate the spinal defecation center, resulting in enhancement of colorectal motility.…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to responses in male rats, in which both serotonergic and dopaminergic pathways are activated (Naitou et al 2018). It is well known that dopamine in the lumbar spinal cord is mainly released by descending neurons projecting from the A11 region of the diencephalon (Skagerberg et al 1982;Koblinger et al 2014;Ozawa et al 2017). Taking into account that the density of descending dopaminergic fibres is lower in females than in males (Pappas et al 2010), the lack of involvement of dopaminergic pathways in female rats would be due to insufficient release of dopamine from the descending fibres.…”
Section: Discussionmentioning
confidence: 83%
“…2014; Ozawa et al . 2017). Taking into account that the density of descending dopaminergic fibres is lower in females than in males (Pappas et al .…”
Section: Discussionmentioning
confidence: 99%
“…Both D1-like and D2-like receptors exist in the rat spinal cord at a high density [184]. There are descending dopaminergic pathways to the spinal dorsal horn from the periventricular posterior region (A11) of the hypothalamus in rats [185,186,187,188]. Intrathecally-administrated apomorphine (a D2 receptor agonist) inhibited thermally and chemically evoked noxious responses in rats ([189]; see [190] for review).…”
Section: Effects Of Other Endogenous Pain Modulators On Synaptic Tmentioning
confidence: 99%